2021
DOI: 10.2174/1389202922666210219113220
|View full text |Cite
|
Sign up to set email alerts
|

Study on Transcriptional Responses and Identification of Ribosomal Protein Genes for Potential Resistance against Brown Planthopper and Gall Midge Pests in Rice

Abstract: Background: Our previous studies have revealed the roles of ribosomal protein (RP) genes in the abiotic stress responses of rice. Methods: In the current investigation, we examine the possible involvement of these genes in insect stress responses. We have characterized the RP genes that included both Ribosomal Protein Large (RPL) and Ribosomal Protein Small (RPS) subunit genes in response to infestation by two economically important insect pests, the brown planthopper (BPH) and the Asian rice gall midge (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Ribosomal proteins have also been linked to galling diseases, such as clubroot, where changes in ribosomal proteins are used as markers to detect the geographic origin of the strain as well as its virulence (Laila et al, 2017, Javed et al, 2023). Ribosomal proteins in rice have also been linked to resistance against gall midges (Moin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Ribosomal proteins have also been linked to galling diseases, such as clubroot, where changes in ribosomal proteins are used as markers to detect the geographic origin of the strain as well as its virulence (Laila et al, 2017, Javed et al, 2023). Ribosomal proteins in rice have also been linked to resistance against gall midges (Moin et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Ribosome proteins in rice have also been linked to resistance against gall midges (Moin et al . 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Ribosomal proteins have also been linked to galling diseases, such as clubroot, where changes in ribosome proteins are used as markers to detect the geographic origin of the strain, as well as its virulence (Laila et al 2017;Javed et al 2023). Ribosome proteins in rice have also been linked to resistance against gall midges (Moin et al 2021).…”
Section: Potential Mechanisms For Parasitoid-induced Gall Formationmentioning
confidence: 99%
“…Ribosomes are a vital part of cell replication, responsible for protein synthesis, and play an important role in controlling cell growth, division, and development [70]. A large number of studies have demonstrated that in addition to forming ribosomes and participating in protein biosynthesis [71], ribosomal proteins are involved in chloroplast development [72], translation regulation [73], and other processes. This study further analyzed the downregulated ribosome synthesis pathway with significant enrichment.…”
Section: Degs Involved In the Pathway Of Ribosomementioning
confidence: 99%